Integrating cancer rehabilitation and lifestyle medicine: a proposed partnership and case example from the RISE cancer survivorship clinic. - Sleight, Alix G.; Weschler, Stephen B.; Jones, Jennifer M.; Wood, Kelley C.; Pergolotti, Mackenzi; Williams, Courtney P.; Brick, Rachelle S.; Lyon, Sarah; Virani, Aneesha; Takata, Sandy C.; Lyons, Kathleen D.; Swartz, Maria C.; et al. (Disability & Rehabilitation, 2026)
Purpose: Cancer mortality is associated with modifiable health behaviors such as physical activity, alcohol intake, and diet; however, it is estimated that only 5-25% of cancer survivors adhere to health behavior recommendations after diagnosis. With the overburdened infrastructure of healthcare in the United States and the high out-of-pocket expenditures for cancer patients, it is challenging for cancer survivors to access personalized lifestyle medicine in many settings. Materials and Methods: In this Perspective, an interdisciplinary team of cancer rehabilitation and lifestyle medicine clinicians outline the potential for synergy between the two fields to illustrate the possibilities for improvement in cancer care when the two disciplines are integrated. Results: We outline key concepts and present a case example from Re-invent, Integrate, Strengthen, Expand (RISE), an occupational therapy-based cancer survivorship clinic employing the tenets of lifestyle medicine in a major urban medical center in the United States. Conclusion: Cancer rehabilitation clinicians are uniquely situated to collaborate with lifestyle medicine clinicians in the assessment of lifestyle-related issues and interventions designed to mitigate these issues. The RISE cancer survivorship clinic provides a practical, real-life example of this collaboration in action. Cancer care throughout the continuum may benefit from an increase in synergistic activities between these two professional domains. IMPLICATIONS FOR REHABILITATION: Lifestyle medicine is an important but underutilized field that can be leveraged to optimize health outcomes for people with a history of cancer. Cancer rehabilitation clinicians are well-situated to collaborate with lifestyle medicine in the assessment of lifestyle-related issues and interventions designed to mitigate these issues. The Re-invent, Integrate, Strengthen, Expand (RISE) Cancer Survivorship Clinic provides a case example of a successful integration of cancer rehabilitation and lifestyle medicine in a major urban medical center and may provide a framework for future clinical collaboration in this area.